Is it possible to achieve bio-equivalence between an oral solid immediate-release and an analogue enteric-coated formulation?. (27th July 2016) - Licht, Dannit; Cohen, Rachel; Spiegelstein, Ofer; Rabinovich-Guilatt, Laura; Zholkovsky, Marina; Gilbert, Adrian; Dressman, Jennifer B; Safadi, Muhammad
Abstract: Objectives: While bioequivalence between enteric-coated and immediate-release formulations can be achieved in terms of AUC, gastric emptying of enteric-coated dosage forms is a stochastic event, usually leading to lower C max values than those observed with the corresponding immediate release. This article examines challenges of developing enteric-coated dosage forms which are bioequivalent to the corresponding immediate-release formulations in terms of both AUC and C max using rasagiline as a model compound. Methods: In vitro drug release profiles of enteric-coated formulations were obtained and compared to those of the immediate-release formulation by dissolution testing. Pharmacokinetics was evaluated in bioequivalence studies in healthy human volunteers after single oral administration of enteric-coated and immediate-release formulations. Key findings: The initial enteric-coated pellet formulation prototype was equivalent in terms of AUC, but differed in C max ; a second formulation prototype, consisting of a single-unit core and enteric-coating film, proved to be bioequivalent to immediate-release rasagiline tablets in terms of AUC and C max . In vitro, it released rasagiline rapidly at a pH of 6.8. Conclusions: Despite differences in gastric emptying between disintegrating immediate-release and enteric-coated solid dosage forms, bioequivalence in pharmacokinetic studies was achieved.